An Attempt of the Synthesis of Recent Knowledge About Mechanisms Involved in Stabilization Function of Geogrids in Infrastructure Constructions. (2017) - Rakowski, Zikmund
Abstract: Geogrids are involved in stabilization projects worldwide for around three decades already. The function has been called for quite a long time as the reinforcement of subbase, base or ballast according to the application. Only recent observations both from laboratories and field prove that it is not the strength which is the factor controlling this function but that certain stiffening of granular material by interlocking is the most important one. The paper describes the mechanism of stabilisation function of geogrids and defines basic influencing properties. The impact of such an approach on theoretical studies and practical applications is described.